125. Characterization of a novel scintillating detector for in vivo dosimetry in MRI guided radiotherapy. (December 2018) - Placidi, L.; Cusumano, D.; D'Agostino, E.; Valentini, V.; De Spirito, M.; Azario, L.
Abstract: Purpose: Optical fibre sensor technology offer numerous advantages over conventional dosimeters, including the use in the MRI environment, as they are non-magnetic and do not cause interface on the image. This study aims to dosimetrically characterize a novel inorganic scintillator detector (DoseWireTM, DoseVue) to evaluate its feasibility for a clinical application in MRI guided radiotherapy. Methods: Experimental setup was realized with a water equivalent slab phantom: the detector was placed orthogonal to the beam source (SAD = 105 cm, SSD = 100 cm), 10 cm thickness slabs were placed below the detector to provide backscattered radiation. The detector holder was realized facing with 1, 5 mm spacing two additional slabs of 1 mm between the 10 cm and 5 cm slabs. MRidian system (ViewRay, three cobalt-60 sources with 0.35 T MRI technology), was used for the detector irradiation. Dose linearity was performed with 10.5 × 10.5 cm 2 field delivering 0.1 Gy, 0.5 Gy, 1 Gy, 2 Gy, 5 Gy and 7.5 Gy. Detector resolution was assessed increasing the delivered dose of the dose linearity test of 0.1 Gy, for each dose levels already delivered. Detector repeatability was estimated repeating the 0.5 Gy delivering set four times with two different Cobalt sources. Finally, field size dependency (2.1 × 2.1 cm 2, 6.3 × 6.3 cm 2, 10.5 × 10.5 cm 2, 14.7 × 14.7 cm 2, 21 × 21 cm 2 ) was investigated delivering 0.5 Gy. Results: Dose linearity and resolution results are shown in Fig. 1. All the other results, are summarized inTable 1 . The detector can resolve 0.1 Gy and it shows a linear dependency within the dose. Repeatability was within 99–100%. Conclusions: A preliminary characterization of the detector has been successfully performed. For its physical properties, the detector response is not influenced by magnetic field, so DoseWire can be a promising detector for in vivo dosimetry in MR-Guided Radiotherapy. Further investigations have been already scheduled, to validate the detector for clinical use, like surface and transmission measurements, evaluation of the electron return effect, quality assurance tests and comparison with a reference ionization chamber.